2008
DOI: 10.2139/ssrn.1128339
|View full text |Cite
|
Sign up to set email alerts
|

Defining Access to Health Care: Evidence on the Importance of Quality and Distance in Rural Tanzania

Abstract: We examine the implications of health seeking behavior on access to quality health care using a unique dataset that combines a household survey from rural Tanzania with the location and quality of all health facilities available to households. Patients do not always visit the nearest facility, but choose from among multiple facilities, improving the quality of care they receive by bypassing low quality facilities. Recognizing this behavior alters the projected benefits to health interventions, reducing the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…We follow the implementation used in Leonard, Masatu, and Vialou (2007). An appendix to this paper details this process (Klemick, Leonard, and Masatu 2009).…”
Section: Creating Competence and Performance Scoresmentioning
confidence: 99%
“…We follow the implementation used in Leonard, Masatu, and Vialou (2007). An appendix to this paper details this process (Klemick, Leonard, and Masatu 2009).…”
Section: Creating Competence and Performance Scoresmentioning
confidence: 99%
“…Some health care seekers often bypass lower quality service to attend facilities providing higher quality services (Klemick et al, 2009). However in a study by Noor et al (2003) it was found that there is a correlation between actual and potential/ theoretical usage of public health facilities in Kenya.…”
Section: Spatial Distribution Of Mental Health Care Centresmentioning
confidence: 99%
“…Source: Klemick, Leonard, and Masatu 2009. Note: The figure shows the outcomes of 1,399 health episodes from a household survey in the rural Arusha region in Tanzania for which the patient has completed treatment matched with the average quality provided at the first facility visited for that illness.…”
Section: Percent Of Episodesmentioning
confidence: 99%
“…An example of an instrument that can be used is included in the annex as table 7A.2 (Klemick, Leonard, and Masatu 2009). If the research is tracking the presence of individuals, an instrument that records the names of personnel would be necessary.…”
Section: Instrumentsmentioning
confidence: 99%